Thermal analysis of two and three-gate sand casting mould - Lim, Alex Kheng Booi (2001)
A study of thermal characteristics of the molten metal in sand casting process had been carried out. This comprises of experimental work and modeling of casting process. Two sand molds are fabricated using the carbon dioxide-silicate method. One of them has 2 gates and the other one has 3 gates. Data of temperature distribution can be obtained by detecting the temperature changes at thermocouples from various predetermined location of the sand mold. Presence of molten metal can be known by observing the drastic changes of temperature at a particular point and therefore the flow characteristics was studied. The data is presented in a graphical format and is compared with the calculated result produced from modeling program called Thermnet. The Thermnet program is a simulation program for thermal analysis. This simulation program is Network technique based. Comparison of modeling and experimental results are also presented. Finally, base on these data, weak point of the sand mold design is being pointed out and proposal for a better design is made.